PREVALENCE OF FELINE CORONAVIRUS CASES DURING AUGUST-SEPTEMBER 2025 AT VETOPET 1 ANIMAL CLINIC, CIKARET, WEST JAVA - Muh Rifky Rachman; Tetty Barunawati Siagian (Buletin Veteriner Udayana, 2026)
Feline Coronavirus (FCoV) can mutate into Feline Infectious Peritonitis (FIP), which has high morbidity and mortality rates in cats worldwide and is transmitted through the fecal-oral route. The highest incidence of FCoV infection occurs in Europe (47.6%), including Germany (100%). Research on the prevalence of FCoV in Indonesia has not been widely reported. The objective of this study was to determine the prevalence of FCoV infection at Vetopet 1 Animal Clinic. Primary data were obtained from rapid combo test results (GIA, FCoV, FPV) confirmed positive for FCoV infection by veterinarians, and secondary data was obtained from the cats' medical records. The prevalence of FCoV during the period of August–September 2025 at Vetopet 1 Animal Clinic, based on breed category, was 69% in non-domestic breeds (χ² = 0.044; P<0.05). Based on sex, the prevalence was 69% in male cats (χ² = 0.025; P<0.05). Kittens showed a prevalence of 59% (χ² = 0.002; P<0.05). Based on living environment, indoor, semi-indoor, and outdoor cats showed a prevalence of 50%, while households owning more than one cat showed a prevalence of 78%. The results of this study indicate that the prevalence of FCoV infection at Vetopet 1 Animal Clinic falls within the moderate category.